Facile construction of dual‐response super‐resolution probes for tracking organelles dynamics - Daili Liu; Guiqian Fang; Yanfeng Wang; Caicai Meng; Zhidong Liu; Qixin Chen; Xintian Shao (Exploration)
Abstract Super‐resolution imaging techniques, such as structured illumination microscopy (SIM), have enabled researchers to obtain nanoscale organelle‐level outputs in living systems, but they impose additional stringent requirements on fluorescence probes. However, high‐performance, custom‐designed SIM probes that can explain underlying biological processes remain unavailable. Herein, a customizable engineering toolkit is developed for the facile assembly of SIM probes suitable for subcellular component detection. This toolkit is used to customize a fluorescent molecule, CPC (coumarin–phenylhydrazine–carboxyl), capable of simultaneously monitoring peroxynitrite (ONOO−) and polarity distribution in mitochondria and lipid droplets (LDs), respectively, through functional ON–OFF mechanisms. The customized CPC molecule demonstrated excellent imaging capabilities under SIM, enabled the successful localization of multiple organelles, and reliably tracked the distribution of different components, thus facilitating the study of the interplay between organelles. Using CPC, the physical transition of intracellular LDs is demonstrated from heterogeneity to homogeneity. This was specifically observed during ferroptosis where the polarity of the LDs increased and their morphology became more contracted. Furthermore, the loss of LDs functionality could not counteract the accumulation of ONOO− within the mitochondria, leading to the decoupling of mitochondrial LDs during ferroptosis. These results confirmed the potential mechanism of LDs dysfunction and decoupling triggered via cumulative mitochondrial oxidative stress during ferroptosis. To summarize, this toolkit will be a powerful tool for examining subtle variations among components during the interplay between different organelles, thus offering novel avenues for understanding and treating related diseases.